-3x-83=7(3x-5)

Simple and best practice solution for -3x-83=7(3x-5) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3x-83=7(3x-5) equation:



-3x-83=7(3x-5)
We move all terms to the left:
-3x-83-(7(3x-5))=0
We calculate terms in parentheses: -(7(3x-5)), so:
7(3x-5)
We multiply parentheses
21x-35
Back to the equation:
-(21x-35)
We get rid of parentheses
-3x-21x+35-83=0
We add all the numbers together, and all the variables
-24x-48=0
We move all terms containing x to the left, all other terms to the right
-24x=48
x=48/-24
x=-2

See similar equations:

| (19x+4)+(24x+4)=180 | | 10x+A100=-10 | | 2(3x+12)=3x+24 | | 9x-25+104+104=180 | | (98-y)6=12 | | 8‐3x=‐13 | | 5(j-91)=40 | | 3/2x+1/2x=5.5+5/2 | | 55-o=42 | | 4x+5-9x=10 | | 9x+3-7x+25=20 | | 2(6y-7)=70 | | 3/2x+1/2x=5/1/2+5/2 | | x+16=4x+1=3x+9 | | 4x+5-9x=10* | | 3x^{2}+13=-134 | | 6m+24=24+6m | | 5(j−91)=40 | | 8(4w+9)/5=-5 | | 2(3x+12)=6x+24 | | 9y+2y+12=67 | | 3/2x+1/2x=51/2+5/2 | | 12=6(y−98) | | 3x=1/2(54) | | 72=8(z+1) | | 2+1y=y+8 | | 4(r+7)=4+2r | | -4p-8=(-8+5p) | | 3x=1/254 | | 12x-5=5+12x | | 3-8c=43 | | 40=4f+12 |

Equations solver categories